Genetic pollution of a threatened native crested newt species through hybridization with an invasive congener in the Netherlands. (April 2015) - Meilink, Willem R.M.; Arntzen, Jan W.; van Delft, Jeroen J.C.W.; Wielstra, Ben
Highlights: Case study of hybridization between a threatened native and an invasive species. Differences in sensitivity to genetic pollution for population genetics programs and datasets. Observed displacement with hybridization of native by invasive species. Considerations for management of genetic pollution discussed. Abstract: Genetic pollution of a native species through hybridization with an invasive species poses an insidious conservation threat. To expose genetic pollution, molecular methods employing multilocus data are required. We present a case study of genetic pollution via hybridization of a native crested newt species, Triturus cristatus, by the invasive Triturus carnifex on the Veluwe in the Netherlands. We sequenced 50 nuclear markers by next generation sequencing and one mitochondrial marker by Sanger sequencing for four populations from the native range of both parent species and eleven ponds on the Veluwe. We use three population genetic approaches (HIest, BAPS and Structure) to determine the genetic composition of the Veluwe newts based on all nuclear markers, a subset of 18 diagnostic markers and the complementary 32 non-diagnostic markers, with and without parental populations. BAPS underestimates genetic pollution, whereas Structure is comparatively accurate compared to HIest, although Structure's relative advantage decreases with the diagnosticity of the markers. Data simulation confirms these findings. Genetic composition of the Veluwe ponds ranges from completely native, via different degrees of genetic admixture, to completely invasive. The observed hybrid zone appears to be bimodal, suggesting negative selection against hybrids. A genetic footprint of the native species is present in invasive populations, evidencing that the invasive locally replaced the native species. Genetic pollution is currently confined to a small area, but the possibility of further expansion cannot be excluded. Removal of genetic pollution will not be easy. We emphasize the need for legal guidance to manage genetic pollution.